SWOT Analysis of the Development Strategy for the Limpakuwus Pine Forest Tourist Attraction - Diana Indra Dewi; Sri Rum Giyarsih; Djaka Marwasta (PT FORMOSA CENDEKIA GLOBAL, 2023)
Every year, a large number of tourists visit the Limpakuwus Pine Forest tourist attraction. Overcrowding in tourist attraction areas is caused by the high number of visitors, which can harm environmental conditions and tourist comfort. The aim of this research is to investigate the use of SWOT analysis in the tourism management of the Limpakuwus Pine Forest tourist attraction. This research method uses a survey method by taking a sample of a number of tourists, and managers of Limpakuwus Pine Forest tourist attractions. The type of data collected consists of primary data and secondary data obtained through observation and interviews with respondents, as well as literature, selects through related agencies. Based on the results, the Limpakuwus Pine Forest tourism industry is currently in a consolidation phase, during which its growth is accelerating. From the time it first opened until now, this phase has been marked by an increase in visitors, who are now at their peak. Because of the excessive density of tourist attractions, managers are expected to be able to implement environmental limits in order to maintain environmental conditions and visitor fulfillment